Writing scientific thesis/dissertation in biology field: Problem of conclusion writing - Salman, Huda D. (Iraqi Journal of Cancer and Medical Genetics, 2013)
A conclusion chapter is written at the end of thesis or dissertation by postgraduate students to express the meaning of results. The conclusion text should be written according to the most acceptable standard guidelines for scientific writing. Conclusions must be written in clear, concise, fully supported by the results obtained, based on fact and logic, and far from exaggeration or speculation. This project included studying and analyzing of the conclusion chapter text in 124 written theses and dissertations by postgraduate students (master and doctor of philosophy) in biological sciences from different Faculties and different Departments. The study also involved interviewing 114 postgraduate students from those fields to obtain their opinion about how to write a conclusion text. All students of both degrees wrote their conclusion in separated numbered statements and no conclusion written in paragraphs. Almost all students tended to repeat all their results in short sentences without any innovation comments. All students showed significant lack in conclusion writing knowledge and they hadn’t any idea about how to write a conclusion text; they just wrote the conclusion chapter in order to fulfill the requirements or obtaining the degree. Almost all students neither tried to read any article or guidelines for how to write a conclusion chapter nor took specific course for writing process in their curriculum. Students tried to mimic the writing style of previous graduate students regardless of that writing style was correct or not. The study concludes that almost all postgraduate students have no knowledge or skill in scientific writing process especially in conclusion text writing. Therefore, it is strongly recommended be to re-evaluate the postgraduate curriculum in order to involve courses that can improve the level scientific writing of theses or dissertations.